We are all migrants - Jaan Valsiner (Comparative Migration Studies, 2022)
Abstract Migration is the basis for development—economic, social, and psychological. In this paper I will examine borders on migration that entail the ambivalent relating by the societal context of migration to the act of movement of the people who become migrants, and their counterparts (“counter-migrants”) who do not. My focus on the issue stems from my theory of Cultural Psychology of Semiotic Dynamics that can deal with the process of becoming, being, and feeling as “migrant” or “counter-migrant”. A societal rule system is fortified by the system of social representations of the people who—by the act of moving from one place to another—are designated to become migrants by the rule systems of the non-migrants. Cultural psychology contributes to the study of the emerging prejudices and ways of their overcoming by the non-migrant local recipients as well as to the ambivalences of the persons who move to the relating with the social role “migrant” and its overcoming. Historically speaking—we as the species of Homo sapiens are all migrants—only at differing times and circumstances.